What causes gender differences in the participation and intensity of lifelong learning? - Huber, Peter [Verfasser]; Huemer, Ulrike [Verfasser] (WIFO, 2009)
"We use recent advances in the statistical analysis of Oaxaca-Blinder decompositions for non-linear models to analyse the contribution of individual variables to total gender differences in participation and duration of training. Results suggest that effects stemming from the intra-houshold division of labour contribute significantly to gender differences, burt that segregation of the labour market as well as differences in the access to training by tenure, age, occupation, profession and sectors are more important." (öibf, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; G 2.4.5 Gender Mainstreaming; I 2.2.1 Westeuropa; Lebenslanges Lernen; Bildungsbeteiligung; Geschlechtsspezifische Faktoren; Geschlechterverteilung; Österreich